Prevalence of Contact Allergens in Best-Selling Ophthalmic Products. Issue 4 (July 2021) - Om, Anjali; Yeung, Howa; de la Feld, Salma
Abstract : Background: Ophthalmic products are a common but often overlooked contributor to allergic contact dermatitis. Frequency of allergenic ingredients in over-the-counter ophthalmic products has not been well characterized. Objective: The purpose of this study was to determine the prevalence of allergenic ingredients in most commonly bought eye lubricants and contact lens solutions. Methods: A product list of Amazon.com 's best-selling ophthalmic products was curated by searching for "Best Sellers in Eye Drops, Lubricants & Washes" and "Best Sellers in Contact Lens Care Products." For exploratory analysis, indication, price, consumer ratings, number of reviews, and US Food and Drug Administration approval status were recorded. The products' ingredients were compiled using NLM DailyMed, and products that had 1 or more allergens or relevant cross-reactors on either the 2018 American Contact Dermatitis Society Core Allergen Series or the 2015–2016 North American Contact Dermatitis Group Standard Allergen Series were noted. Results: Forty-eight percent (n = 49) of the total products, (57.8% [n = 37] of eye lubricants, and 31.6% [n = 12] of contact lens solutions) had 1 or more allergens or associated cross-reactors. Identified allergens were benzalkonium chloride, propylene glycol, sorbic acid, amidoamine, sorbitan sesquioleate, chlorhexidine digluconate, lanolin alcohol, parabens, benzyl alcohol, and butylated hydroxytoluene. Conclusions: Awareness of potential allergens is crucial to diagnosing allergic contact dermatitis to ophthalmic products and helping patients navigate online pharmacological chaos.